THE EFFECT OF THE STATE OF ACUTE AND CHRONIC STRESS ON THE PROTECTIVE MECHANISMS OF THE BODY. (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2024)
This article explores the impact of both acute and chronic stress on the body's protective mechanisms, including the immune, endocrine, and nervous systems. Acute stress, characterized by a short-term response to immediate threats, can initially enhance certain immune functions, providing temporary boosts in resilience. However, chronic stress, sustained over extended periods, leads to persistent activation of stress pathways that can deplete bodily resources and weaken defenses, increasing vulnerability to infections, autoimmune disorders, and chronic diseases.